MO456: Renal and Major Clinical Outcomes After Nephrectomy in Patients With Pre-Existing Chronic Kidney Disease (ON-CKD Study). (3rd May 2022) - Schleef, Maxime; Roy, Pascal; Paparel, Philippe; Colombel, Marc; Badet, Lionel; Guebre-Egziabher, Fitsum
Abstract: BACKGROUND AND AIMS: Partial nephrectomy (PN) has progressively replaced radical nephrectomy (RN) whenever feasible for renal tumors. However, its effects on renal outcomes are less known in patients with pre-existing chronic kidney disease (CKD) or with solitary kidney (SK). We aimed to assess renal and major clinical outcomes after PN or RN in patients with moderate to severe CKD or SK. METHOD: We included all surgical procedures conducted between 2013 and 2018 in the Hospices Civils de Lyon, in patients with last pre-operative estimated glomerular filtration rate (eGFR) <60mL/min/1.73m², or with SK. Exclusion criteria were eGFR < 15mL/min/1.73m² or dialysis, RN on SK, ablative therapy. Demographic, tumors and surgeries characteristics were collected, as well as eGFR 1 month and 1 year after surgery. Main outcome was a composite criterion including CKD progression or major cardio-vascular events or death, assessed 1 year after surgery. Predictors of the main outcome were determined using multivariate analyses. RESULTS: We included 173 procedures (67 RN and 79 PN on CKD patients, 27 PN on SK patients). Patients undergoing RN were older, had bigger tumors and higher T stages on TNM classification. Preoperative estimated glomerular filtration rate (eGFR) and CKD stages were not different between the groups. One year after surgery, PN was associated with less occurrence of the main composite outcome compared to RN (42.9% versus 70.7%, P < 0.01). On multivariate analysis, independent risk factors for the main outcome were postoperative AKI (no AKI as reference; AKI stage 1 odds ratio (OR) = 8.68, 95% confidence interval (CI) 3.23–23.33; AKI stage 2 OR = 23.50, 95% CI 2.33–236.51; AKI stage 3 OR = 28.87, 95% CI 4.77–167.61) and bigger tumor size (OR = 1.21/cm, 95% CI 1.02–1.45), while preoperative eGFR was not (Table 1 ). Compared to pre-operative values, eGFR significantly decreased both after RN or PN 1 month after surgery (eGFR loss -12mL/min 1.73m² after RN P < 0.001, −3mL/min/1.73m² after PN, P < 0.05) and this decrease remained stable 1 year after surgery (eGFR loss -11mL/min/1.73m² after RN, P < 0.001, −3mL/min/1.73m² after PN, P < 0.05), but renal function was better preserved after PN than after RN at 1 month (P < 0.05) or 1 year (P < 0.01) (Figure 1 ). CONCLUSION: In moderate to severe CKD patients, PN was associated with less risk of CKD progression or major cardio-vascular event or death 1 year after surgery, compared to RN. Postoperative AKI was the major determinant of clinical and renal outcomes.